PENGARUH WAKTU PEMANGKASAN PUCUK DAN KONSENTRASI ETHEPON TERHADAP PERTUMBUHAN DAN HASIL TANAMAN MENTIMUN (Cucumis sativus L.) KULTIVAR WULAN - Deden Deden; Dodi Budirokhman; Ading Sugandi (Agroswagati Jurnal Agronomi, 2020)
The experiment was conducted to know the effect of pruning time shoots and concentration ethepon on the growth and yield of cucumber (Cucumis sativus L.) cultivar Wulan. The experiment was conducted at Sangkanurip Village, Cigandamekar District, Kuningan, West Java Province, from March until May 2018. The experimental design was used Randomized Complete Block Design (RBD) with factorial pattern. Each treatment was repeated three timer. The treatment consisted two factors. The first factor is time pruning shoots which consist three levels : P0 (without pruning), P1 (age 15 DAP pruning), P2 (age 20 DAP pruning), while the second factor is the concentration ethepon which consists four levels : E0 (0 ppm), E1 (100 ppm), E2 (200 ppm), E3 (300 ppm). The results showed that there was a significnt interaction effect between pruning time shoots and concentration ethepon on plant high (27 and 24 days after planting), number of leafs (27, 34, and 41 days after planting), and total weight per plant. Independently, time pruning shoots gave significant effect on plant high (41 days after planting), number of male flowers, number of fruit per plant. While concentration ethepon gave a real effect on number of male flowers, number of female flowers, ratio of female flowers and number of fruits. There is a significant correlation between the number of leafs age 27 DAP (days after planting) the results of the total weight per plot.